Supernatants of intestinal luminal contents from mice fed high‐fat diet impair intestinal motility by injuring enteric neurons and smooth muscle cells. Issue 1 (24th September 2020) - Nyavor, Yvonne; Brands, Catherine R.; Nicholson, Jessica; Kuther, Sydney; Cox, Kortni K.; May, George; Miller, Christopher; Yasuda, Allysha; Potter, Forrest; Cady, Joshua; Heyman, Heino M.; Metz, Thomas O.; et al.
Abstract: Background: Damage to enteric neurons and impaired gastrointestinal muscle contractions cause motility disorders in 70% of diabetic patients. It is thought that enteric neuropathy and dysmotility occur before overt diabetes, but triggers of these abnormalities are not fully known. We tested the hypothesis that intestinal contents of mice with and without high‐fat diet‐ (HFD‐) induced diabetic conditions contain molecules that impair gastrointestinal movements by damaging neurons and disrupting muscle contractions. Methods: Small and large intestinal segments were collected from healthy, standard chow diet (SCD) fed mice. Filtrates of ileocecal contents (ileocecal supernatants; ICS) from HFD or SCD mice were perfused through them. Cultured intact intestinal muscularis externa preparations were used to determine whether ICS and their fractions obtained by solid‐phase extraction (SPE) and SPE subfractions collected by high‐performance liquid chromatography (HPLC) disrupt muscle contractions by injuring neurons and smooth muscle cells. Key Results: ICS from HFD mice reduced intestinal motility, but those from SCD mice had no effect. ICS, aqueous SPE fractions and two out of twenty HPLC subfractions of aqueous SPE fractions from HFD mice blocked muscle contractions, caused a loss of nitrergic myenteric neurons through inflammation, and reduced smooth muscle excitability. Lipopolysaccharide and palmitate caused a loss of nitrergic myenteric neurons but did not affect muscle contractions. Conclusions & Inferences: Unknown molecules in intestinal contents of HFD mice trigger enteric neuropathy and dysmotility. Further studies are required to identify the toxic molecules and their mechanisms of action. Abstract : High fat diet (HFD) ingestion results in dysbiosis, altered gut microbiota and host interactions, and compromised intestinal barrier integrity. This results in the generation of neurotoxic and anti‐motility molecules, which damage intestinal neurons and muscle. This damage leads to disrupted neurotransmission and muscle contractions, which impair intestinal motility and exacerbates dysbiosis and altered interactions between microbiota and host.